Systematic Microwave-Assisted Postsynthesis of Mn-Doped Cesium Lead Halide Perovskites with Improved Color-Tunable Luminescence and Stability - Yaheng Zhang; Chao Fan; Jianghong Tang; Gaoming Huang; Xinfa Qiang; Yu Fu; Wenjuan Zhou; Juan Wu; Shouqiang Huang (Nanomaterials, 2022)
The metal doping at the Pb2+ position provides improved luminescence performance for the cesium lead halide perovskites, and their fabrication methods assisted by microwave have attracted considerable attention due to the advantages of fast heating and low energy consumption. However, the postsynthetic doping strategy of the metal-doped perovskites driven by microwave heating still lacks systematic research. In this study, the assembly of CsPbBr3/CsPb2Br5 with a strong fluorescence peak at 523 nm is used as the CsPbBr3 precursor, and through the optimization of the postsynthetic conditions such as reaction temperatures, Mn2+/Pb2+ feeding ratios, and Mn2+ sources, the optimum Mn2+-doped product (CsPb(Cl/Br)3:Mn) is achieved. The exciton fluorescence peak of CsPb(Cl/Br)3:Mn is blueshifted to 437 nm, and an obvious fluorescence peak attributing to the doped Mn2+ ions at 597 nm is obtained. Both the CsPbBr3 precursor and CsPb(Cl/Br)3:Mn have high PLQY and stability because there are CsPb2Br5 microcubic crystals to well disperse and embed the CsPbBr3 nanocrystals (NCs) in the precursor, and after Mn2+-doping, this structure is maintained to form CsPb(Cl/Br)3:Mn NCs on the surface of their microcrystals. The exploration of preparation parameters in the microwave-assisted method provides insights into the enhanced color-tunable luminescence of the metal-doped perovskite materials.